Upaya Jaksa dalam Penyelidikan Tindak Pidana Korupsi (Studi pada Kejaksaan Negeri Malang) - Muhammad Riski; Setiyono Setiyono; Teguh Suratman (Postgraduate University of Merdeka Malang, 2021)
This study aims to analyze the efforts of prosecutors in investigating corruption crimes and to examine and analyze the obstacles faced by prosecutors in investigating corruption crimes and the efforts to overcome them. Methodologically, this research belongs to the type of criminological research where this approach is intended to find out the causes and efforts of prosecutors in investigating Corruption Crimes as well as the obstacles faced by prosecutors in Corruption Crime Investigations and efforts to overcome them. Using an interactive analysis model or Interactive Model of Analysis, it was found that the prosecutor's efforts were carried out in investigating a corruption case, carried out through a series of processes in the form of Notification of the Commencement of Investigation so that no one corruption case was investigated by two different agencies. the investigation can run efficiently, effectively and well, the collection of evidence, exposure will determine the conclusion drawn whether the criminal case will be forwarded to the prosecution stage or an additional investigation will be carried out to complete and perfect the investigation until the submission of files to the public prosecutor. In the case of corruption, the investigating prosecutor faces several obstacles, namely: Time management, coordination, and the resistance from the perpetrators of corruption.DOI: https://doi.org/10.26905/mlj.v2i2.7158